Highly Flexible Organic Nanofiber Phototransistors Fabricated on a Textile Composite for Wearable Photosensors. (8th February 2016) - Lee, Moo Yeol; Hong, Jayeon; Lee, Eun Kwang; Yu, Hojeong; Kim, Hyoeun; Lee, Jea Uk; Lee, Wonoh; Oh, Joon Hak
Abstract : Highly flexible organic nanofiber phototransistors are fabricated on a highly flexible poly(ethylene terephthalate) (PET) textile/poly(dimethylsiloxane) (PDMS) composite substrate. Organic nanofibers are obtained by electrospinning, using a mixture of poly(3, 3 ″′ ‐didodecylquarterthiophene) (PQT‐12) and poly(ethylene oxide) (PEO) as the semiconducting polymer and processing aid, respectively. PDMS is used as both a buffer layer for flattening the PET textile and a dielectric layer in the bottom‐gate bottom‐contact device configuration. PQT‐12:PEO nanofibers can be well‐aligned on the textile composite substrate by electrospinning onto a rotating drum collector. The nanofiber phototransistors fabricated on the PET/PDMS textile composite substrate show highly stable device performance (on‐current retention up to 82.3 (±6.7)%) under extreme bending conditions, with a bending radius down to 0.75 mm and repeated tests over 1000 cycles, while those prepared on film‐type PET and PDMS‐only substrates exhibit much poorer performances. The photoresponsive behaviors of PQT‐12:PEO nanofiber phototransistors have been investigated under light irradiation with different wavelengths. The maximum photoresponsivity, photocurrent/dark‐current ratio, and external quantum efficiency under blue light illumination were 930 mA W −1, 2.76, and 246%, respectively. Furthermore, highly flexible 10 × 10 photosensor arrays have been fabricated which are able to detect incident photonic signals with high resolution. The flexible photosensors described herein have high potential for applications as wearable photosensors. Abstract : Highly flexible organic nanofiber phototransistors are prepared using a poly(ethylene terephthalate) textile/poly(dimethylsiloxane) composite and photoresponsive electrospun polymer nanofibers as flexible substrate and photoactive layers, respectively. The devices show stable electrical performance under extreme bending conditions; and flexible 10 × 10 photosensor arrays exhibit high‐resolution photosignal mapping, which have a high potential for applications as wearable photosensors.